DINAMIKA PERKEMBANGAN ARABISME DI INDONESIA: (Dynamics of the Development of Arabism in Indonesia) - Muhamad Yusuf Sidiq (Raqib: Jurnal Studi Islam, 2025)
This study aims to determine the development of Arabism in Indonesia. The approach used in this study is to use a scientific approach, how to see the development of Arabism in Indonesia based on concrete data that exists in society. Of course with a descriptive analytical method using Pierre Bourdieu's Habitus theory. Habitus theory has a meaning in it as a habit, but the habits that occur do not come from the internal actor itself but from the external (social environment). The results of the study show that there are several factors that influence the development of Arabism in Indonesia, including, First, Education Factors, Second, Community Environmental Factors, Third, Family Environmental Factors, fourth, Religious factors.